Motivational Interviewing and Glycemic Control in Adolescents With Poorly Controlled Type 1 Diabetes: A Randomized Controlled Pilot Trial - Tuomaala, Anna-Kaisa; Hero, Matti; Tuomisto, Martti T.; Lähteenmäki, Maria; Miettinen, Päivi J.; Laine, Tiina; Wehkalampi, Karoliina; Kiiveri, Sanne; Ahonen, Pekka; Ojaniemi, Marja; Kaunisto, Kari; Tossavainen, Päivi; et al. (Frontiers in Endocrinology, 2021)
A multicenter randomized controlled pilot trial investigated whether motivational interviewing (MI) by diabetes physicians improves glycemic control and variability in the context of follow-up for adolescent patients with poorly controlled type 1 diabetes. Patients (n = 47) aged 12 to 15.9 years who showed poor glycemic control (HbA1c >75 mmol/mol/9.0%) were randomized to standard education (SE) only or MI+SE, with study physicians randomized to employ MI+SE (N = 24 patients) or SE only (N = 23). For one year of follow-up, the main outcome measurements were obtained at three-month visits (HbA1c) or six-monthly: time in range (TIR) and glycemic variability (CV). Mean adjusted 12-month change in HbA1c was similar between the MI+SE and SE-only group (-3.6 vs. -1.0 mmol/mol), and no inter-group differences were visible in the mean adjusted 12-month change in TIR (-0.8 vs. 2.6%; P = 0.53) or CV (-0.5 vs. -6.2; P = 0.26). However, the order of entering the study correlated significantly with the 12-month change in HbA1c in the MI+SE group (r = -0.5; P = 0.006) and not in the SE-only group (r = 0.2; P = 0.4). No link was evident between MI and changes in quality of life. The authors conclude that MI’s short-term use by diabetes physicians managing adolescents with poorly controlled type 1 diabetes was not superior to SE alone; however, improved skills in applying the MI method at the outpatient clinic may produce greater benefits in glycemic control.